Dampak Penerapan Masalah Audit Utama di Indonesia - Ariadi, Deni; Jasmine, Jasmine; Oktavia, Veronica (CV. Lafadz Jaya, 2023)
Disclosure of the value of the main audit issues or also called Key Audit Matters (KAM) is determined from the quality of audit information. This study aims to provide an understanding of the main audit issues so as to obtain communicative value. The research was carried out with the publication of the Draft Auditing Standard Exposure (SA) regarding the adoption of ISA 701 containing on Communicating Main Audit Matters in the Independent Auditor's Report. This study examines whether ISA 701 issued by the International Auditing and Assurance Standards Board is able to influence the auditor's decision. Research also provides information related to what is the cause of the decrease in the communicative value of disclosing major audit issues. The results of the study indicate that there is support for the implementation of SA 701 which is planned in Indonesia because this is related to an increase in the communicative value of the auditor's report. The research will be useful in preparing for the implementation of SA 701 for auditors and report users in interpreting disclosures from KAM which will support the implementation of SA 701 in Indonesia.